Beyond the house job: Time to rethink medical training? - Cheema, Zoreiz Zahid; Siddiq, Nadia (Journal of the Pakistan Medical Association, 2025)
Medical knowledge is expanding, diseases are becoming more complex, and healthcare challenges are growing—so why is our approach to training doctors decades behind? Dr. Bradley D. Freeman, in his commentary, highlights the inconsistency between the minimum postgraduate training required for licensure and the actual years of training necessary to ensure physician competency 1. He argues that doctors are granted independent licensure in many jurisdictions after just one year of training, despite evidence indicating that full competency in primary care disciplines typically requires at least three years. Similarly, Dr. Janis M. Orlowski reinforces that a one-year internship is outdated and misaligned with modern medical education standards, which emphasise competency-based progression over fixed training durations 2. This global perspective underscores the urgency of reforming Pakistan’s medical training system, which remains rooted in an outdated model that inadequately prepares fresh medical graduates for independent practice. The one-year house job provides basic clinical exposure but lacks the structured training necessary for developing strong clinical decision-making and procedural skills 3. This deficiency compromises patient care, escalates referrals to tertiary hospitals, and overburdens specialized centers while leaving peripheral healthcare facilities underutilized 4. To address these shortcomings, Pakistan must transition to a mandatory three-year residency program before granting independent licensure. Internationally, models like the U.S. residency system have demonstrated that structured multi-year training enhances physician competency, improves patient outcomes, and reduces unnecessary hospital referrals5. A structured residency not only strengthens clinical expertise but also optimizes healthcare resource utilization—an essential consideration in resource-limited settings like Pakistan. It’s time for Pakistan to reconsider and reform its postgraduate medical training system to align with global standards. Implementing a structured three-year residency will not only elevate healthcare standards but also equip future physicians with the skills and confidence needed for independent practice. A modernized, competency-driven training approach is not merely an improvement—it is a necessity for building a competent, efficient, and sustainable healthcare system.